KONTRIBUSI SEKTOR UMKM PADA UPAYA PENGENTASAN KEMISKINAN DI INDONESIA - MEIDA RACHMAWATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Poverty is still a big issue that occurs in almost all over the world, including third world countries like Indonesia. This study aims to find a theoretical framework for the possibility of solving the problem of poverty through MSMEs. This research is a literature study or literature study with actual data taken from credible sources. Data is 'dialogued' with references to relevant theories such as the circle of poverty theory. The results show that theoretically MSMEs are very likely as an exit strategy for poverty in Indonesia. MSMEs have very strong probabilities as representative ways out for poverty alleviation in this country.